Development of social studies evaluation media based on minimum competency assessment "MELUAS" questions for students at SMPN 1 Besuki - Nirmala, Pratidina Okta; Ratnawati, Nurul (Jurnal Inovasi Teknologi Pendidikan, 2024)
Minimum competency assessment is one of the government's efforts to improve students' literacy and numeracy skills. For this reason, teachers must support it by applying it to learning activities. This research aims to develop social studies evaluation media based on minimum competency assessment "MELUAS" questions. The method uses RnD with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects used to assess the suitability of this product were 32 students in class VIII C at SMP Negeri 1 Besuki. Based on the questionnaire, the responses show that MELUAS is "very suitable" for use by students. The existence of MELUAS can increase users' reading literacy, attract students to conduct evaluation activities, and encourage the quality of students' enthusiasm. Recommendations for further research are to develop evaluation media based on minimum competency assessment questions, equip them with videos and animations on the question text stimulus, and add features that discuss the correct answers.